Qasam Menurut Imam Abu Hamid Al-Din Al-Farahi: Studi atas Kitab Im’an Fi Aqsam Al-Qur’an - Faturrohman Faturrohman; Mardian Idris Hrp (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to examine two points. First, the interpretation of Imam Abu Hamid al-Din al-Farahi contemplate using the method of thought (bil ra’yi). Second, the interpretation of Imam Abu Hamid al-Din al-Farahi fixed with the element and no combining between the element of riwayah and element of dirayah. This research implicates to find out the typology or with the another interpretation of Imam Abu Hamid al-Din al-Farah interpret the verses of qasam with the noble Quran, the hujjah especially in interpretation of qasam in the noble Quran.This research used the qualitative method, or to find out and observe the librarian research study. This research found the interpretation of Imam Abu Hamid al-Din al-Farahi about the verses of qasam. even though in noble Quran. This research revealed that the interpretation of Imam Abu Hamid al-Din al-Farahi about the verses of qasam in the noble Quran is the noble Quran itself. Qasam was written in the verses of qasam. The interpretation Alquran with Sunnah. the interpretation of the noble Quran with riwayah and the interpretation of the noble Quran with riwayat tabi’in and Ulama. And another commitment with the construction is dominated by typology of bil ra’yi. the interpretation of Imam Abu Hamid al-Din al-Farahi unexcavated between element of riwayah and elemen of dirayah, and the stands of reproduction. and hujjah based on the meaning words, combined muqsam ‘alayh. combined with the verses, hadis, and the ulama’s perception in the combining of interpretation at prophet’s historical.